Strategi Pembelajaran Berbasis Kecerdasan Majemuk (Multiple Intelligences) - Liandy, Septian (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2023)
This study aims to analyze the strategy of learning based on Multiple Intelligences in elementary schools, focusing on its effectiveness and implementation challenges. The research method is qualitative, using library research. The research subjects consist of various academic literatures, such as journals, books, articles, and educational policy documents published in the last five years. The research object includes concepts, theories, and practices of implementing Multiple Intelligences-based learning strategies in elementary schools. Data collection is conducted through systematic literature review, and data analysis uses the interactive analysis model by Miles, Huberman, and Saldana. The findings reveal that the implementation of this strategy can enhance students' motivation and learning outcomes by accommodating the diversity of intelligences. However, the main challenge faced is the limited understanding of teachers and the available facilities in elementary schools. The study concludes that to optimize the implementation of this strategy, intensive teacher training and adequate technological support are necessary.